Mediating role of resilience between successful aging and acculturation among older Korean immigrants In the United States - Lee, Jaewon (Advances in Social Sciences Research Journal, 2020)
Background: This study was to investigate how acculturative stress affects older Korean immigrants' successful aging and whether resilience can play a mediator's role to the sample population's successful aging or not. The research design was a cross-sectional survey using three valid and reliable scales such as Successful Aging Scale, Acculturative Stress Scale, and Resilience Scale. A research shows that there is no or minimum correlation between acculturative stress and successful aging (Choi & Thomas, 2009). However, it was hypothesized that although there was a weak correlation between acculturative stress and successful aging, once the resilience involved as a mediator, the correlation would be stronger. Methods: The study was designed as a self-administered survey research using the scales mentioned above. One hundred and two (N=102) older Koreans who currently enrolled in Adult Health Care Centers in Los Angeles, CA, participated in this study. Multiple Regression, Correlation, ANOVA, and t-test was administered to analyze the collected data. Results: The results indicated that there was a positive but weak correlation between acculturative stress and the sample population's successful aging rate (r = .252, p<.05). Interestingly, when resilience intervened as a mediator, the correlation between acculturation and successful aging was increased to (r = .622, p<.05). Therefore, the study discovered that the resilience was able to play a mediator's role between acculturative stress and successful aging among the older Korean immigrants. Implications: The findings can be directed to social work researchers and practitioners to help educate the ethnic older adults in the community on the social and behavioral importance of the positive aspects of aging such as successful aging and healthy aging to increase the chance of community member's longevity. Future research will include other ethnic and immigrant older populations in the community to show internal and external validity of the study related to successful aging, acculturative stress, and resilience.